Media Pembelajaran Animal Metamorphosis dilengkapi Multimedia Interaktif dalam Menunjang Perkuliahan IPA SD - Bagus Rahmad Wijaya; Andika Adinanda Siswoyo; Ade Cyntia Pritasari (Universitas Nahdlatul Ulama Pasuruan, 2020)
Organizing innovative and quality education in order to produce professional and competitive primary school educators is the vision of the elementary school teacher education program in Trunojoyo Madura University. One form of educational innovation is to develop learning media that supports educators. Learning media is important in the learning process. The presence of learning media is able to bridge the obscurity of the material presented. One of the materials needed for its delivery is animal metamorphosis. Characteristics of animal metamorphosis material are difficult to present in class and in a short amount of time. The objectives of the research carried out are to: (1) produce learning media for metamorphosis of animals and interactive multimedia in elementary science subjects; and (2) learning the feasibility level of learning media for animal metamorphosis and interactive multimedia in elementary science subjects. This research uses research and development methods. The development model used is 4D. The research subjects were third semester students in the Natural Sciences elementary school. The instruments of data collection used consisted of questionnaire sheets. The results showed that the metamorphosis of animal media and interactive multimedia was appropriate to be used with very good categories in terms of media and material aspects.